La archidiócesis de Zaragoza en los años veinte / The Archdiocese of Zaragoza in the 1920s - Juan Ramón Royo García (Studia et Documenta, 2025)
The diocese of Zaragoza, the fifth largest in Spain, experienced a time of change during the 1920s due to the assassination of its archbishop Cardinal Soldevila in 1923, a long vacancy of his seat, and the beginning of the pontificate of Archbishop Domenech (1925-1955). It was a time of apparent brilliance, with the establishment of numerous religious communities and an important laity (which at the end of the decade would begin to organize itself in Catholic Action). But the diocese was already showing symptoms of crisis, with a decrease in vocations and priests to serve parishes and other diocesan institutions.